Dynamic electrical transport in carbon nanotubes and nanodiamond films - Chimowa, George (My University, 2014)
A comprehensive experimental study on alternating current (AC) electrical transport in the three forms of carbon nanotubes (CNTs) and nanodiamond films is presented. It is termed dynamic electrical transport to differentiate it from direct current measurements, which may be referred as static transport. The results and analysis are based on the scattering parameter measurements of a few horizontally aligned single, double, multi-walled carbon nanotubes and nanodiamond films. Which were measured in the frequency range 10 MHz to 65 GHz, at room and cryogenic temperatures using a vector network analyser. The work is motivated by the fact that AC transport in 1D systems has not been fully studied and is not well understood. From direct current measurements, it is known that one dimensional (1D) electrical transport is very different from its two or three dimensional counterpart. This is because adding an electron to a 1D system tends to affect the whole system in ways which to date cannot be fully explained theoretically. CNTs present an ideal platform to study the AC or dynamic transport behaviour of 1D systems because of the high mobility and electrical conductivity at nano-scale. Therefore from the AC complex impedance and conductance, this work demonstrates quantum effects of collectively excited strongly interacting electrons (Luttinger Liquid), which had been predicted theoretically but not observed experimentally using this technique. Ballistic transport at room temperature is also demonstrated by setting the stimulus frequency higher than the scattering rate in the CNTs. A crossover from capacitive to inductive behaviour in the imaginary component of impedance has been shown by improving the CNT-electrode coupling. Furthermore the effect of metal contacts on microwave/ radio frequency transmission is also demonstrated. The results are consolidated by RF simulations, as strong conclusions are drawn. Studies on the dynamic transport in nanodiamond films revealed a crossover from the insulating to semi-metallic regime by nitrogen incorporation. The crossover is explained by considering the changes of the grain boundary morphology. This work shows that AC transport in polycrystalline nanodiamond films is similar to DC transport.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Nanostructured materials.; Nanostructures.; Nanotubes, Carbon content.; Carbon.